Lung adenocarcinoma and adrenocortical carcinoma in a patient with multiple endocrine neoplasia type 1. (2017) - Ohara, Nobumasa; Kaneko, Masanori; Ikeda, Masahiro; Ishizaki, Fumio; Suzuki, Kazuya; Maruyama, Ryo; Komeyama, Takeshi; Sato, Kazuhiro; Togashi, Kenichi; Usuda, Hiroyuki; Yamazaki, Yuto; Sasano, Hironobu; et al.
Abstract: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disorder caused by heterozygous germline mutations in the tumor suppressor gene MEN1, which encodes a nuclear protein, menin. MEN1 is characterized by the combined occurrence of tumors involving the pituitary gland, pancreatic islets, and parathyroid glands. Additionally, patients with MEN1 often exhibit adrenal tumors. Although most MEN1-associated tumors are benign, malignant lesions arising in these endocrine organs have been reported. Additionally, malignant diseases of non-endocrine organs concomitant with MEN1 have also been reported. Here, we report a rare case of a MEN1 patient who exhibited adrenocortical carcinoma (ACC) and lung adenocarcinoma (LAC). A 53-year-old Japanese woman was diagnosed with genetically proven MEN1 that initially manifested as parathyroid, pancreatic, and adrenal tumors. During the course of the disease, she developed LAC harboring the epidermal growth factor receptor gene mutations and cortisol-secreting ACC. Both tumors were surgically resected. The tumor cells were immunohistochemically negative for menin. Studies have suggested a causative link between MEN1 gene mutations and ACC, and menin expression may decrease in MEN1-related ACCs. In contrast, there are few reports suggesting a specific role of MEN1 gene mutations in LAC. Menin is often inactivated in the LACs of patients without MEN1. Thus, our patient's ACC probably occurred as part of MEN1, whereas the latter had no evident etiological association with her LAC. This case demonstrates the need for physicians to consider the potential development of malignant diseases originating from both endocrine and non-endocrine organs in MEN1 patients.